1974
DOI: 10.1192/bjp.124.6.573
|View full text |Cite
|
Sign up to set email alerts
|

A Scale for Predicting Subsequent Suicidal Behaviour

Abstract: Between 1962 and 1970, the male parasuicide (attempted suicide) rate in Edinburgh has doubled, and the rate for women shows a 70 per cent increase (Kreitman, 1972). Of those who are admitted following a parasuicidal act a substantial proportion are readmitted—approximately 15 per cent within 12 months and 25 per cent within three years. Parasuicide is a sign of severe distress, and repetition indicates that the distress has not been adequately alleviated. A means of early identification of the potential repeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
2
1

Year Published

1980
1980
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(55 citation statements)
references
References 5 publications
3
49
2
1
Order By: Relevance
“…At index admission, sociodemographic data concerning gender, age, educational level, employment status and income were examined. The Buglass and Horton Risk of Repetition Scale-a 6-item scale for predicting subsequent suicidal behaviorwas completed, and the person was asked about previous suicidal behavior (Buglass & Horton, 1974). At follow-up, changes in the living situation and civil state were assessed, problems and=or suicidal thoughts were questioned.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…At index admission, sociodemographic data concerning gender, age, educational level, employment status and income were examined. The Buglass and Horton Risk of Repetition Scale-a 6-item scale for predicting subsequent suicidal behaviorwas completed, and the person was asked about previous suicidal behavior (Buglass & Horton, 1974). At follow-up, changes in the living situation and civil state were assessed, problems and=or suicidal thoughts were questioned.…”
Section: Methodsmentioning
confidence: 99%
“…Changes in living situation was not discriminative for non-fatal repetition in this sample, which is in contrast to findings of different studies. Living alone, alone with children, or with others who were not relatives, are known as predictor items for repetition of suicide attempts (Bille-Brahe & Jessen, 1994;Buglass & Horton, 1974;Kreitman & Casey, 1988;Wang, Nielsen, Bille-Brahe et al, 1985). The Edinburgh Risk of Repetition scale (Kreitman & Foster, 1991) defines that a higher risk of repetition is associated with unemployment and with a single, divorced, or separated, civil status.…”
Section: Civil Status and Living Situationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that up to 20% of ideators in a given year make a suicide attempt during that year (Kessler et al, 2005a;Kuo et al, 2001), justifying this focus. We use an actuarial, data-driven approach similar to the approach used successfully to develop prediction models for violent behavior (Dawes et al, 1989;Harris et al, 2004;Harris et al, 2003;Hilton et al, 2004;Mossman, 1994), and less successfully to predict repetitive suicidal behavior (Buglass & Horton, 1974;Corcoran et al, 1997;Hawton & Fagg, 1995;Kreitman & Foster, 1991). We focus on potential risk factors that clinicians can assess quickly using fully structured assessments.…”
mentioning
confidence: 99%
“…But can they be identified before they repeat, and with an accuracy that could be clinically useful? Buglass & Horton (19746) collected data on all patients admitted to the Regional Poisoning Centre in Edinburgh and constructed a scale of six items which discriminated between repeaters and non-repeaters. These were similar to those listed above-(1) previous parasuicide resulting in admission; (2) previous psychiatric treatment as in-patient; or (3) out-patient; (4) alcohol problems; (5) a diagnosis of sociopathy; and (6) not living with relatives.…”
Section: From Correlation To Formal Predictionmentioning
confidence: 99%